The exes : a novel [large type] - Darlington, Leodora (Good morning America book club., 2026)
"Who hasn't wanted to murder an ex--figuratively, at least? In this explosive debut thriller, a woman's seemingly perfect romantic life is on the verge of collapse as she uncovers a hidden history surfacing dark secrets that have deadly consequences. Natalie has only ever wanted to find 'the one.' The perfect man, the happy family she never had. But each time she thinks she is finally getting somewhere, she's bitterly disappointed. Another red line through a list of exes. And that was before the night of the Big Fallout that left her even more alone. Then along comes James--wonderful, handsome James--and Natalie thinks her luck has finally turned. Maybe he's the one for her. Maybe he's the one she's been waiting for all along. Maybe he won't wind up dead. But the harder Natalie tries to be a 'normal' wife, the more world-upending truths are brought to her door, leaving her unsure of who she really is, and much less what she'll do...leaving her to question whether there is a monster within her or whether there is a villain toying with her from the outside. What's the secret story behind Natalie's dead exes? Will she and James survive their marriage? And do either of them deserve to?" -- Provided by publisher.